GLOSARIUM KOSAKATA BAHASA INDONESIA DALAM RAGAM MEDIA SOSIAL - Elvi Susanti (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: This research is tangent to the variety of social media. Social Media is a social media services on the internet that are very popular today in the world, including in Indonesia. The aims this study to describe how the vocabulary in a variety of social media came at once and agreed on by social media users. Vocabulary that affect the development of the Indonesian in the spoken language, especially obtained glossary of terms that developed in social media. This research method uses qualitative research methods as a scientific research. The goal is to understand a phenomenon in the social context naturally with the advanced process of interaction between researchers in-depth communication with the phenomenon under study. The results of this study is the vocabulary used in social media there are based on its creativity without any previous origins. However, there are also derived from foreign languages ​​(English, Korean, Japanese), Indonesian, local language, vocabulary inverted structure, vocabulary already in the dictionary slang and slang that already exists.Abstrak: Penelitian ini bersinggungan dengan ragam media sosial. Media sosial merupakan layanan media sosial di internet yang sangat populer saat ini di dunia, termasuk di Indonesia. The Penelitian ini bertujuan untuk mendeskripsikan bagaimana kosakata dalam ragam media sosial muncul seketika dan disepakati bersama oleh pengguna media sosial. Kosakata itu berpengaruh terhadap perkembangan bahasa Indonesia dalam ragam lisan, khususnya glosarium yang diperoleh dari istilah-istilah yang berkembang di media sosial. Metode penelitian ini menggunakan metode penelitian kualitatif sebagai suatu penelitian ilmiah.Tujuannya adalah untuk memahami suatu fenomena dalam konteks sosial secara alamiah dengan mengedepankan proses interaksi komunikasi yang mendalam antara peneliti dengan fenomena yang diteliti. Hasil penelitian ini adalah kosakata yang digunakan dalam media sosial ada yang berdasarkan kreativitas penggunanya tanpa ada asal-usul sebelumnya. Akan tetapi, ada juga yang berasal dari bahasa asing (Inggris, Korea, Jepang), bahasa Indonesia, bahasa daerah, kosakata yang dibolak-balik susunannya, kosakata yang memang sudah ada dalam kamus bahasa gaul, dan bahasa slang yang sudah ada sebelumnya.Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v3i2.5188